Mexico City’s Creative Districts at the Second Decade of the XXI Century - Mercado Celis, Alejandro (Universidad del Rosario, 2016)
The agglomeration of cultural / creative industries and specialized retail stores in urban districts marked by a rapid urban transformation process has been identified as “Creative Districts”. It has been assumed that these districts are economic clusters in the sense of being an economic system formed by specialized companies and their corresponding labor market. From our point of view these districts are only a visible part of a larger economic cluster operating at the metropolitan scale which includes many different areas, enterprises and jobs. In this paper we discuss the conceptual and methodological problems of bringing the concept of economic cluster or industrial district to the intra-urban geographic scale. In order to confront the idea of ‘creative districts’ as functional economic areas separable from the rest of the metropolitan economy, we apply the methods commonly used in urban studies on creative industries to identify possible creative districts within Mexico City. The identified districts are contrasted in their economic structures to determine if there are indications that indeed they are differentiable and functional economic clusters from the rest of the metropolitan area. We conclude by arguing that the data found sustain the existence of a single metropolitan economic cluster and no small clusters in urban districts.